Pacific subduction coeval with the Karoo mantle plume: the Early Jurasssic Subcordilleran belt of northwestern Patagonia - Rapela, Carlos Washington (2005)
The Early Mesozoic magmatism of southwestern Gondwana is reviewed in the light of new U-Pb SHRIMP zircon ages (181 ± 2 Ma, 181 ± 3 Ma, 185 ± 2 Ma, and 182 ± 2 Ma) that establish an Early Jurassic age for the granites of the Subcordilleran plutonic belt in northwestern Argentine Patagonia. New geochemical and isotopic data confirm that this belt represents an early subduction-related magmatic arc along the proto-Pacific margin of Gondwana. Thus, subduction was synchronous with the initial phase of Chon Aike rhyolite volcanism ascribed to the thermal effects of the Karoo mantle plume and heralding rifting of this part of the supercontinent. Overall, there is clear evidence that successive episodes of calc-alkaline arc magmatism from Late Triassic times until establishment of the Andean Patagonian batholith in the Late Jurassic involved westerly migration and clockwise rotation of the arc. This indicates a changing geodynamic regime during Gondwana break-up and suggests differential rollback of the subducted slab, with accretion of new crustal material and/or asymmetrical ‘scissor-like’ opening of back-arc basins. This almost certainly entailed dextral displacement of continental domains in Patagonia.